Competition between foreign affiliates: Multinational banks internal funding in the crisis - Rainer Frey; Cornelia Düwel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We investigate how the lending activities of a multinational bank s affiliates located abroad are affected by funding difficulties in view of the financial crisis. For this, we consider transaction-induced changes in long-term lending to the private sector of 40 countries by the affiliates of the 68 largest German banks. We find that affiliates local deposits and profitability have been stabilizing loan supply. By contrast, relying on short-term wholesale funding has increasingly proven to be a disadvantage in the crisis, as inter-bank and capital markets froze. Besides, the more an affiliate abroad takes recourse to intra-bank funding in the crisis, the more it becomes dependent on a stable deposit and long-term wholesale funding position of its parent bank. We furthermore detect competition for intra-bank funding across the affiliates abroad as well as an increasing focus on the parent bank s home market activities.
Keywords: G21; F23; F34; 330